Zinc metal recovery method
The method uses an alkaline leachate with ammonium ions to leach zinc and copper, followed by impurity separation and electrolytic deposition to recover high-purity metallic zinc, addressing the challenge of copper contamination in steel manufacturing by-products.
Patent Information
- Application Number
- JP2023095063
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-08
- Publication Date
- 2024-12-19
AI Technical Summary
Existing methods struggle to recover high-purity metallic zinc from leaching treatment objects containing iron, zinc, and copper, which are common by-products in steel manufacturing processes, as they often result in low-quality steel due to copper contamination.
A method involving the use of an alkaline leachate with ammonium ions to leach zinc and copper as ions, followed by impurity separation steps using solvent extraction, electrolytic deposition, and hydrophobic liquid replacement to achieve high-purity metallic zinc recovery.
The method effectively recovers metallic zinc with a purity of 90.00% or more by mass, reducing copper and other impurities, thereby improving the quality of steel produced from recycled materials.
Smart Images

Figure 2024176500000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for recovering metallic zinc from a solid leaching treatment target that contains an iron component and at least zinc and copper in the form of either metal or oxide. [Background technology]
[0002] Scrap, which is a raw material for steel manufacturing, often has a high copper content, mainly due to the inclusion of copper wires used as electric wires and conductors, and other copper or copper alloy parts. Scrap also includes surface-treated steel sheets, such as galvanized steel sheets, which contain a small amount of zinc, a surface treatment component of steel sheets. Ferroscrap includes, for example, scrapped automobiles, scrapped electrical products, machine scraps, and cutting scraps generated during processing.
[0003] Dust, a by-product of the steel manufacturing process, is generated in sintering, blast furnaces, converters, and electric furnaces in integrated steelworks, and is mainly composed of iron, but also contains zinc.Scale is iron oxide that is generated when the surface of steel material is oxidized in hot conditions during continuous casting and hot rolling, and is mainly composed of iron oxide, but may contain small amounts of copper.
[0004] Sludge, a by-product of the steel manufacturing process, is generated during the neutralization of acidic wastewater and plating wastewater produced during the production of galvanized steel sheets. In addition to the iron in the base material, it contains zinc and nickel, which are plating components, and these metals exist as hydroxides.
[0005] Copper is an element that adversely affects the mechanical properties, workability, and other performance of steel products, and if copper-containing scrap is used as a raw material for smelting steel, only low-quality steel can be produced. Therefore, it is preferable to remove copper from scrap, and various copper removal methods have been researched.
[0006] For example, Patent Document 1 discloses a method for producing a leaching solution containing ammine complex ions and a post-leaching solution containing the ammine complex ions and the remainder of the solid leaching object, the method comprising: a leaching step in which a solid leaching object containing an iron component and one or both of copper and zinc in the form of at least one of metal, oxide, hydroxide, and chloride is contacted with a leachate containing an ionized ammonium salt having a pH range of 7.5 to 11.5 in a first sealed container to elute one or both of the copper and zinc in the solid leaching object as ammine complex ions into the leachate; a first solid-liquid separation step in which the post-leaching solution is subjected to solid-liquid separation to separate the post-leaching solution after solid-liquid separation, which is a liquid phase containing the ammine complex ions, from the remainder of the solid leaching object; and a second solid-liquid separation step in which the post-leaching solution after solid-liquid separation is subjected to solid-liquid separation to separate the post-leaching solution after solid-liquid separation into a liquid phase containing the ammine complex ions and the remainder of the solid leaching object. and a leachate regeneration step of adding at least one sulfiding agent selected from the group consisting of sodium, sodium hydrogen sulfide, potassium sulfide, potassium hydrogen sulfide, magnesium sulfide, and calcium sulfide to decompose ammine complex ions in the leaching solution after solid-liquid separation, thereby precipitating one or both of copper and zinc as solid sulfides and regenerating an ionized ammonium salt to obtain a regenerated solution containing the solid sulfide and the ammonium salt; and a second solid-liquid separation step of separating the regenerated solution into a solid sulfide containing one or both of copper and zinc and a regenerated solution after solid-liquid separation that is a liquid phase containing the ionized ammonium salt, wherein the regenerated solution in the liquid phase separated in the second solid-liquid separation step is used as the leachate to be used in the leaching step.
[0007] Patent Document 2 also describes a method for extracting metals such as zinc, lead, copper, and cadmium from flue dust from an electric steelmaking furnace, comprising the steps of: (a) treating the flue dust with an aqueous solution of ammonium chloride and sodium chloride to dissolve the zinc, cadmium, and copper as ammine complex salts and the lead as a chloro complex salt; (b) separating the resulting solution from the solid residue; and (c) treating the solution obtained in (b) with zinc powder to precipitate the metals more noble than zinc by substitution in an electrochemical series; (d) separating the solution from the precipitate obtained in (c); (e) electrolytically collecting the zinc from the solution obtained in (d) by depositing the zinc at the cathode and generating oxygen at the anode in an electrolytic cell; (f) further treating flue dust from the electric furnace with the zinc-depleted solution obtained by (e); and (g) recycling the residue from (b) to the electric furnace to reduce iron oxides and fumigate the zinc contained in the residue as zinc ferrite.
[0008] Patent Document 3 discloses a method for separating and recovering zinc from ferroscrap, which comprises step 1 of treating ferroscrap including galvanized steel with an aqueous solution containing ammonia and ammonium salt in the presence of oxygen to dissolve the zinc in the scrap as an ammine-zinc complex, and then separating the scrap from the aqueous solution, and step 2 of heating the aqueous solution obtained in step 1 to evaporate the ammonia content, and then recovering the precipitated zinc salt.
[0009] Patent Document 4 discloses a method for separating and recovering copper, iron, etc. from motor scraps, which comprises heating or shot blasting small motor scraps or iron clad material containing copper or a copper alloy to destroy the enamel coating on the copper wire and make the copper wire easier to leach, then putting the scraps into a leaching tank, selectively eluting only copper with a leaching solution containing divalent copper ammine as a leaching agent, and recovering copper from the leachate containing the eluted copper.
[0010] Patent Document 5 also describes a method for extracting an aqueous solution containing copper(I) ions by treating an aqueous solution containing copper(I) ions, precious metal ions, and metal ions other than copper(I) ions, which comprises the steps of: (a) contacting an aqueous solution containing copper(I) ions, precious metal ions, and metal ions other than copper(I) ions with metallic copper to precipitate and separate and remove the precious metals; (b) contacting the aqueous solution with an organic phase to selectively transfer metal ions other than copper(I) ions to the organic phase, leaving the aqueous solution containing copper(I) ions in the aqueous phase; and (c) separating the aqueous phase from the organic phase. (d) washing the organic phase containing metal ions other than copper(I) ions with water; (e) stripping the metal ions other than copper(I) ions from the organic phase containing metal ions other than copper(I) ions and regenerating the organic phase; and (f) recycling the regenerated organic phase to the step (b).
[0011] Patent Document 6 also describes an electrolytic cell separated by a cation exchange membrane into a cathode chamber equipped with a cathode and an anode chamber equipped with a diamond electrode. Supplying a solution containing metal ions to the cathode chamber; Supplying a solution containing a reduced oxidant to the anode chamber; A voltage is applied between the cathode and the diamond electrode to deposit a metal on the cathode surface in the cathode chamber, and to regenerate the oxidant in the solution in the anode chamber. A method for producing a metal is disclosed.
[0012] Patent Document 7 also describes a process for recovering tin by adding calcium carbonate to a solution containing tin, and recovering the tin contained in the solution by precipitating it into a compound containing calcium stannate, The tin recovery method disclosed is characterized in that the tin recovery step is performed at a pH in the range of 11.0 or more and 13.5 or less. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] JP 2018-178201 A [Patent Document 2] Japanese Patent Application Publication No. 5-255772 [Patent Document 3] Japanese Patent Application Publication No. 5-271820 [Patent Document 4] Japanese Patent Application Publication No. 6-240373 [Patent Document 5] JP 2006-57137 A [Patent Document 6] JP 2014-40639 A [Patent Document 7] JP 2020-196913 A Summary of the Invention [Problem to be solved by the invention]
[0014] In recent years, from the viewpoint of reusing recovered metallic zinc, there has been a demand for recovering high-purity metallic zinc from leaching treatment targets that contain at least iron components, zinc, and copper, such as iron scrap.
[0015] Therefore, an object of the present disclosure is to provide a method for recovering metallic zinc capable of recovering high-purity metallic zinc from a leaching treatment target containing at least iron, zinc, and copper. [Means for solving the problem]
[0016] The present inventors have conducted extensive research into a method for recovering high-purity metallic zinc from a solid leaching treatment target that contains iron components and at least zinc and copper in the form of either metal or oxide, and as a result have come to disclose this invention.
[0017] The gist of the report is as follows: <1> A method for recovering metallic zinc from a solid leaching treatment target that contains an iron component and at least one of zinc and copper in the form of metal and oxide, comprising: a leaching step of contacting the object of leaching treatment with an alkaline leaching solution containing ammonium ions and having a pH of 7.5 to 14.0 to obtain a leaching solution in which the zinc and copper are leached into the alkaline leaching solution as zinc ions and copper ions; an impurity separation step of subjecting the post-leaching solution to a copper separation operation for separating the copper ions to obtain a zinc ion-containing solution containing the zinc ions; a zinc electrolytic deposition step of reducing and electrolytically depositing the zinc ions from the zinc ion-containing solution to recover metallic zinc having a purity of 90.00% by mass or more; The method for recovering metallic zinc comprising the steps of: <2> The leaching treatment object further contains tin in metallic form. <1> The method for recovering metallic zinc according to claim 1. <3> The leaching step is a step of obtaining a post-leaching solution by leaching the zinc, copper and tin into the alkaline leaching solution having a pH of 12.5 to 14.0 as zinc ions, copper ions and tin ions, The impurity separation step is a step of subjecting the leaching solution to a tin separation step of separating the tin ions into at least one of calcium stannate and magnesium stannate by adding at least one salt selected from the group consisting of calcium or magnesium carbonate, hydroxide, oxide, chloride, formate, and acetate prior to the copper separation step, and subjecting the leaching solution that has been subjected to the tin separation step to the copper separation step. <2> The method for recovering metallic zinc according to claim 1. <4> The copper separation operation in the impurity separation step is an operation of mixing the post-leaching solution with an organic solvent containing an extractant for extracting copper ions, extracting the copper ions into the extractant, and separating the copper ions based on the difference in specific gravity, thereby separating the copper ions. <1> ~ <3> The method for recovering metallic zinc according to any one of claims 1 to 7. <5> The copper separation operation in the impurity separation step is an operation of separating the copper ions by precipitating the copper ions from the post-leaching solution by electrolytic deposition, <1> ~ <3> The method for recovering metallic zinc according to any one of claims 1 to 7. <6> The copper separation operation in the impurity separation step is an operation of separating the copper ions by adding one or both of hydrogen sulfide and sulfide ions to the post-leaching solution to adjust the oxidation-reduction potential and precipitating the copper ions as copper sulfide. <1> ~ <3> The method for recovering metallic zinc according to any one of claims 1 to 7. <7> In the zinc electrodeposition step, the zinc ion-containing liquid has a pH of 7.5 to 14.0. <1> ~ <6> The method for recovering metallic zinc according to any one of claims 1 to 7. <8> After the impurity separation step and before the zinc electrodeposition step, an extraction step of mixing the zinc ion-containing liquid obtained in the impurity separation step with an organic solvent containing an extractant for extracting zinc ions and allowing the mixture to stand, thereby extracting the zinc ions into the organic solvent to obtain a zinc ion-containing organic solvent; a back-extraction step of mixing the zinc ion-containing organic solvent with an acidic aqueous solution and allowing the mixture to stand, thereby back-extracting the zinc ions into the acidic aqueous solution to obtain a zinc ion-containing acidic aqueous solution, The zinc electrodeposition step uses the zinc ion-containing acidic aqueous solution as the zinc ion-containing liquid. <4> ~ <6> The method for recovering metallic zinc according to any one of claims 1 to 7. <9> The copper separation operation in the impurity separation step is an extraction operation in which the post-leaching solution is mixed with an organic solvent containing an extractant for extracting zinc ions and copper ions, and the mixture is allowed to stand, thereby extracting the zinc ions and the copper ions into the organic solvent to obtain an organic solvent containing zinc ions and copper ions; a back-extraction operation in which the zinc ion and copper ion-containing organic solvent is mixed with an acidic aqueous solution and allowed to stand, thereby back-extracting the zinc ion and the copper ion into the acidic aqueous solution to obtain an acidic aqueous solution containing zinc ion and copper ion; The copper ions are separated by electrolytic deposition from the zinc ion- and copper ion-containing acidic aqueous solution to obtain a zinc ion-containing acidic aqueous solution containing the zinc ions. The zinc electrodeposition step uses the zinc ion-containing acidic aqueous solution as the zinc ion-containing liquid. <1> ~ <3> The method for recovering metallic zinc according to any one of claims 1 to 7. <10> The zinc ion- and copper ion-containing acidic aqueous solution has a pH of −1.0 to 4.0. <9> The method for recovering metallic zinc according to claim 1. <11> a hydrophobic liquid replacement step, which is performed after the leaching step, of contacting a hydrophobic liquid with a residue of the leaching treatment target object remaining after the zinc and copper have been leached into the alkaline leaching solution in the leaching step, and replacing the alkaline leaching solution adhering to a surface of the residue with the hydrophobic liquid; <1> ~ <10> The method for recovering metallic zinc according to any one of claims 1 to 7. <12> The boiling point of the hydrophobic liquid at normal pressure is 40°C to 95°C. <11> The method for recovering metallic zinc according to claim 1. Effect of the Invention
[0018] According to the present disclosure, a method for recovering metallic zinc can be provided that can recover high-purity metallic zinc from a leaching treatment target that contains at least iron, zinc, and copper. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a flow diagram illustrating each step of a method for recovering metallic zinc according to an embodiment of the present disclosure. [Diagram 2] 1 is a graph for explaining a Sn seepage region. [Diagram 3] 1 is a graph showing a change in metal ion concentration in an alkaline leaching solution due to the addition of calcium carbonate. [Figure 4] 1 is a graph showing a change in metal ion concentration in an alkaline leaching solution due to the addition of calcium oxide. [Diagram 5]1 is a graph showing the relationship between pH during extraction and extraction rate with respect to copper separation conditions. [Figure 6] 1 is a graph showing the relationship between pH and extraction rate during stripping with respect to copper separation conditions. [Figure 7] 1 is a graph showing the potential of the working electrode (or cathode) during deposition of each metal with respect to copper separation conditions. [Figure 8] 1 is a table showing the measurement results of changes in metal concentration depending on pH and oxidation-reduction potential for copper separation conditions. [Figure 9] 1 is a graph showing the measurement results of changes in metal concentration depending on pH and oxidation-reduction potential in relation to copper separation conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, embodiments of the present disclosure will be described in detail.
[0021] In this specification, unless otherwise specified, a numerical range expressed using "~" means a range that includes the numerical values before and after "~" as the lower limit and upper limit. However, when there is a statement such as "more than" or "less than", it means that at least one of the lower limit and upper limit values is not included. In numerical ranges described in stages, the upper limit or lower limit value described in a certain numerical range may be replaced with the upper limit or lower limit value of another numerical range described in stages. In a numerical range, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. The term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved.
[0022] <Metallic zinc recovery method> A method for recovering metallic zinc according to an embodiment of the present disclosure is a method for recovering metallic zinc from a solid leaching treatment target that contains an iron component and at least zinc and copper in the form of either metal or oxide.
[0023] Here, each step of the method for recovering metallic zinc according to the embodiment of the present disclosure will be described with reference to the flow chart shown in FIG.
[0024] The method for recovering metallic zinc includes: [1] a leaching step; [2] an impurity separation step; and [3] a zinc electrolytic deposition step. [1] In the leaching step, [0] the object to be leached is contacted with an alkaline leachate containing ammonium ions and having a pH of 7.5 to 14.0 to obtain a leachate in which zinc and copper are leached into the alkaline leachate as zinc ions and copper ions. [2] In the impurity separation process, the post-leaching solution is subjected to a copper separation operation to separate copper ions, thereby obtaining a zinc ion-containing solution containing zinc ions. [3] In the zinc electrolytic deposition process, zinc ions are reduced from a zinc ion-containing solution and electrolytically deposited to recover metallic zinc.
[0025] The metallic zinc recovery method according to an embodiment of the present disclosure can recover high-purity metallic zinc from a leaching treatment target that contains at least iron, zinc, and copper by going through the above-mentioned steps.
[0026] <[0] Leaching treatment target> The object of leaching treatment contains an iron component, and also contains at least zinc and copper in the form of either metal or oxide, as shown in [0]-(1) and [0]-(2) of Figure 1. The object of leaching treatment may further contain tin in the form of metal, as shown in [0]-(2) of Figure 1.
[0027] Examples of materials to be leached in the present disclosure include scrap, which is a raw material for steel production, and scale, dust, and sludge, which are by-products of the steel production process.
[0028] <[1] Leaching process> In the leaching step, the object of leaching treatment is contacted with an alkaline leachate containing ammonium ions and having a pH of 7.5 to 14.0 to obtain a leachate in which zinc and copper are leached into the alkaline leachate as zinc ions and copper ions.
[0029] -Separation of nickel and iron during the leaching process In an alkaline leachate containing ammonium ions, copper and zinc generate ammine complex ions and are easily dissolved. In contrast, iron has a greater tendency to ionize than copper, but its surface is passivated and is hardly dissolved. By utilizing these properties of copper, zinc, and iron, copper and zinc can be selectively leached from the object of leaching treatment. In the object of leaching treatment, such as iron scrap, there are parts where the iron is oxidized, and scale or iron oxide particles peel off from the oxidized parts, but these also hardly dissolve in the leachate.
[0030] Furthermore, even if the object of leaching treatment contains lead, gold, silver, etc., lead, gold, and silver do not form ammine complexes, so they are hardly dissolved in the leaching solution. Furthermore, when the leaching treatment object contains metallic nickel or a nickel compound, metallic nickel and nickel oxide among the nickel compounds, nickel oxide, nickel hydroxide, and nickel chloride, do not dissolve in the alkaline leaching solution because they do not form ammine complexes, whereas nickel hydroxide and nickel chloride dissolve in the alkaline leaching solution because they form ammine complexes.
[0031] In addition, when the material to be leached contains metallic zinc or a zinc compound, metallic zinc and zinc compounds such as zinc oxide, zinc hydroxide, zinc chloride, and zinc ferrite (ZnFe 2 O 4 ), zinc ferrite does not dissolve in alkaline leaching solutions because it does not form ammine complexes. However, metallic zinc, zinc oxide, zinc hydroxide, and zinc chloride form ammine complexes and dissolve in alkaline leaching solutions.
[0032] In addition, when the leaching treatment target contains metallic copper or a copper compound, metallic copper and copper compounds such as copper oxide, copper hydroxide, copper chloride, and copper ferrite (CuFe 2 O 4 ), copper ferrite does not dissolve in alkaline leaching solutions because it does not form ammine complexes. However, metallic copper, copper oxide, copper hydroxide, and copper chloride form ammine complexes and dissolve in alkaline leaching solutions.
[0033] Iron scrap, which is a typical example of a leaching treatment target, mainly includes nickel-containing stainless steel and surface-treated steel plate plated with zinc-nickel alloy. The nickel contained in nickel-containing stainless steel is mostly an alloy with iron and chromium, and is contained in the base material of the steel, so it does not leach into the alkaline leachate. The nickel content in the zinc-nickel alloy plating is about 10 to 16 mass%, which means that it is mostly metallic zinc. This metallic zinc in the plating is leached into the alkaline leachate, but the metallic nickel in the plating cannot form an ammine complex ion, so it precipitates in the alkaline leachate as a solid content consisting of fine particles. As described above, after removing the leaching treatment objects such as iron scrap from the leachate after leaching by an operation such as magnetic attraction, the leachate remaining in the leaching tank can be subjected to a solid-liquid separation operation such as filtration to separate the SS components (suspended matter: for example, iron oxide, nickel powder, etc.) in the leachate. In this way, almost no nickel ions or iron ions dissolve in the alkaline leachate from iron scrap, which is a typical example of a leaching treatment object.
[0034] Leaching process operations In the leaching process, the leaching treatment object containing copper and zinc in one or more of the metal and oxide forms is placed in a sealed container, for example, a container with a sealed gas phase, and immersed in the leaching solution in the sealed container containing an ammonium salt. As a result, as shown in the following (formula 1), copper and zinc react with ammonium ions and NaOH in the leaching solution in the sealed container, and are oxidized to divalent ions to generate ammine complex ions and dissolve. At this time, oxygen is used as an oxidizing agent and consumed. This reaction is likely to proceed in an alkaline range of pH 7.5 to pH 14.0. More preferably, it is likely to proceed in an alkaline range of pH 9.5 to pH 10.5.
[0035] Me+2(NH 4 ) 2 SO 4 +2NaOH+1 / 2O 2 →Me(NH 3 ) 4 SO 4 +Na 2 SO 4 +3H 2 O -(1 set) (wherein Me is Cu or Zn)
[0036] In addition, in the leaching solution in a sealed container containing ammonia (ammonium ions), copper and zinc generate ammine complex ions and dissolve easily, whereas iron, although it has a greater tendency to ionize than copper, hardly dissolves because its surface is passivated. By utilizing these properties of copper, zinc, and iron, copper and zinc can be selectively leached from the object of leaching treatment.
[0037] Furthermore, copper and zinc in dust and scale often exist as metals, oxides, or chlorides, while copper and zinc in sludge often exist as hydroxides. When copper and zinc exist as hydroxides, formula (1) becomes formula (1-1), and no oxygen is consumed. Similarly, in the case of oxides and chlorides, no oxygen is consumed.
[0038] Me(OH) 2 ↓+2(NH 4) 2 SO 4 +2NaOH →Me(NH 3 ) 4 SO 4 +Na 2 SO 4 +4H 2 O - (formula 1-1) (wherein Me is Cu or Zn)
[0039] When the leaching treatment target, which is made up of copper and zinc metals, is placed in a sealed container, the reaction (1) proceeds until the oxygen in the sealed container is consumed, and when most of the oxygen is consumed, the reaction (1) stops. Therefore, the oxygen initially present in the sealed container is consumed, and the copper and zinc in the leaching treatment target, which is made up of copper and zinc metals, become ammine complex ions and are eluted to a certain extent.
[0040] Completion of the leaching process (oxygen concentration) In the closed vessel during the leaching process, the dissolved oxygen in the leaching solution or Cu 2+ The ions oxidize the copper and zinc metals, which then react with the ammonium ions in the leachate to form ammine complex ions. The ammine complex reaction occurs easily and takes very little time, but the oxidation reaction of the copper and zinc metals is slow and takes a long time. On the other hand, the dissolved oxygen in the leachate is in equilibrium with the oxygen concentration in the gas phase, and it can be said that the dissolved oxygen concentration in the leachate and the oxygen concentration in the gas phase are almost proportional to each other.
[0041] In order to determine whether or not the leaching of copper and zinc from the leaching treatment object has been completed, it is necessary to determine whether or not the ammine complexation reaction has been completed. Since the ammine complexation reaction is rate-determining, the completion of the oxidation reaction can be determined by continuously or intermittently measuring the oxygen concentration in the gas phase or the dissolved oxygen concentration in the leachate.
[0042] It is preferable to feed an oxygen-containing gas (oxygen or a gas containing oxygen) into the sealed container to oxidize the metal. At this time, it is preferable to control the presence or absence of feeding oxygen or a gas containing oxygen and the amount thereof so that the dissolved oxygen concentration in the leachate in the sealed container is a predetermined value or more within the range of 1 to 40 mg / L, and the oxygen concentration in the gas phase in the sealed container is a predetermined value or more within the range of 2 to 98 volume%. In other words, it is preferable to control the presence or absence of feeding oxygen-containing gas into the leachate when at least one of the following conditions is satisfied: when the dissolved oxygen concentration in the leachate falls below a predetermined value A within the range of 1 to 40 mg / L, and when the oxygen concentration in the gas phase in the sealed container falls below a predetermined value B within the range of 2 to 98 volume%, and it is also preferable to control the amount thereof. In addition, the leaching process can be determined to be completed when the state in which the dissolved oxygen concentration in the leaching solution in the sealed container is equal to or higher than a predetermined value A and the state in which the oxygen concentration in the gas phase in the sealed container is equal to or higher than a predetermined value B continue for a predetermined period of time or more without blowing in an oxygen-containing gas. The predetermined time is preferably within a range of, for example, 3 to 60 minutes.
[0043] Ammonia concentration As the ammine complexation reaction progresses during the leaching process, the free ammonia concentration (NH 3 The concentration of ammonia present as fr-NH 3(also written as "concentration"). ) decreases, and accordingly, the ammonia concentration in the gas phase in the sealed container also decreases. In addition, the ammonium ion concentration in the leachate in the sealed container is in equilibrium with the free ammonia concentration in the leachate in the sealed container at a certain pH, and the free ammonia concentration in the leachate in the sealed container is in equilibrium with the ammonia concentration in the gas phase in the sealed container, so it can be said that the ammonium ion concentration in the leachate in the sealed container is in a proportional relationship with the ammonia concentration in the gas phase in the sealed container. If the free ammonia concentration in the leachate in the sealed container becomes too low, the ammine complexation reaction is difficult to proceed. In addition, if the free ammonia concentration in the leachate in the sealed container becomes too high, water is discharged at the same time when copper sulfide, zinc sulfide, and the leachate after removing copper and zinc are discharged, which will be described later, but the water also contains ammonia components and is taken out of the system, which reduces the economic efficiency. Therefore, it is preferable to appropriately control the free ammonia concentration in the leachate in the sealed container. Specifically, the free ammonia concentration in the leachate in the sealed container is preferably in the range of 3 to 50 g / L, and more preferably in the range of 5 to 20 g / L.
[0044] In addition, since the free ammonia concentration in the leachate in the sealed container is in a nearly equilibrium relationship with the ammonia concentration in the gas phase in the sealed container, the ammonia concentration in the gas phase in the sealed container is preferably in the range of 0.6 to 12% by volume, and more preferably in the range of 1.2 to 4.8% by volume.
[0045] - If it contains tin The material to be leached may contain, in addition to iron, zinc and copper, tin in metallic form (i.e., metallic tin). When the object of leaching treatment further contains tin, it is preferable to use a leaching solution having a pH of 12.5 to 14.0 when contacting the object of leaching treatment with an alkaline leaching solution containing ammonium ions in the leaching step, which allows a post-leaching solution to be obtained in which zinc, copper and tin have been leached into the alkaline leaching solution as zinc ions, copper ions and tin ions.
[0046] Examples of tin-containing iron scrap that are the subject of leaching treatment include tin-plated steel sheets and tin-zinc alloy-plated steel sheets. The tin plating layer in tin-plated steel sheets is mostly made of metallic tin, and the tin-zinc alloy plating layer in tin-zinc alloy-plated steel sheets contains, for example, about 90% tin.
[0047] Here, the Sn leaching region will be described. The following experiment was carried out to confirm the pH at which zinc, copper and tin can be leached from the leaching treatment object into the alkaline leaching solution as zinc ions, copper ions and tin ions. Specifically, copper powder, zinc powder and tin powder were placed in an alkaline leaching solution containing ammonium ions with an adjusted pH, and the amount of each metal leached was measured in the presence of dissolved oxygen, resulting in Figure 2. As can be seen from Figure 2, by using an alkaline leaching solution adjusted to a pH range of 12.5 to 14.0, copper, zinc, and tin can be leached into the leaching solution at the same time. On the other hand, if the pH is less than 12.5, the amount of tin leached out is reduced. One method for raising the pH of the leaching solution to 12.5 or higher is to add a large amount of strong alkali such as sodium hydroxide or potassium hydroxide.
[0048] However, even if the object of leaching treatment further contains tin, it may be removed by other known methods instead of leaching it into the leachate, or a post-leaching solution may be obtained without leaching tin. In this case, a leachate having a pH of 7.5 to 14.0 can be used as the alkaline leachate.
[0049] <[2] Impurity separation process> In the impurity separation step, the post-leaching solution containing at least zinc ions and copper ions is subjected to a copper separation operation for separating copper ions to obtain a zinc ion-containing solution containing zinc ions. When tin is further leached into the alkaline leaching solution as tin ions in the leaching step, the leaching solution is subjected to a tin separation operation prior to the copper separation operation in the impurity separation step.
[0050] ·[2]-(0) Tin separation operation In the tin separation operation in the impurity separation process, at least one salt selected from the group consisting of calcium or magnesium carbonates, hydroxides, oxides, chlorides, formates, and acetates (hereinafter also referred to as a "tin ion precipitant") is added to the post-leaching solution containing at least zinc ions, copper ions, and tin ions to separate the tin ions as at least one of calcium stannate and magnesium stannate.
[0051] Here, in order to confirm the conditions for separating tin by adding calcium oxide or calcium carbonate, the following experiment was carried out. An ammonia-containing alkaline leaching simulation solution containing stannate ions and other metal ions was prepared. More specifically, copper chloride, zinc chloride, sodium stannate, and nickel chloride were dissolved in the solution, and the pH was adjusted to 13.2 with NaOH to prepare an ammonia-containing alkaline leaching simulation solution (1.52 mol-NH 3 To this simulated liquid, sodium sulfide containing sulfide ions, or calcium oxide or calcium carbonate containing Ca ions were added, and the precipitation of each metal ion was measured, and Figures 3 and 4 were obtained. FIG. 3 is a graph showing the change in metal ion concentration in the alkaline leaching solution due to the addition of calcium carbonate, and FIG. 4 is a graph showing the change in metal ion concentration in the alkaline leaching solution due to the addition of calcium oxide.
[0052] As can be seen from Figures 3 and 4, as the amount of calcium oxide or calcium carbonate added increases, tin ions can be precipitated as calcium stannate, the tin concentration in the simulated liquid decreases, and the calcium concentration in the simulated liquid increases accordingly. On the other hand, the concentrations of zinc, copper, and nickel in the simulated liquid did not change. This shows that calcium carbonate or calcium oxide can precipitate tin ions while suppressing the precipitation of metal ions other than tin. There was almost no change in pH, and it was pH13.1 to pH13.2.
[0053] In addition, when calcium carbonate was added, as shown in Figure 3, it was not possible to precipitate all of the tin even when about 14 times the amount of calcium carbonate was added relative to the amount of tin. In contrast, when calcium oxide was added, as shown in Figure 4, it was possible to precipitate almost all of the tin by adding about 5 times the amount of calcium oxide relative to the amount of tin. In other words, from the viewpoint of recovering metallic zinc of higher purity, it is preferable to use calcium oxide as a tin ion precipitating agent in the tin separation operation. Furthermore, a method of first adding calcium carbonate and then adding calcium oxide is more effective.
[0054] The pH of the simulated liquid, calcium carbonate slurry, and calcium oxide slurry were pH13.2, pH9.5, and pH11.8, respectively, with the simulated liquid having the highest pH. Therefore, it is presumed that calcium oxide has a higher solubility than calcium carbonate in the simulated liquid, that is, a higher calcium ion supplying capacity, and therefore the use of calcium oxide resulted in more tin ions being precipitated. Therefore, it is considered that the lower the pH of the leachate, the more the amount of tin ions that can be precipitated can be increased.
[0055] In addition to calcium carbonate and calcium oxide, calcium hydroxide, calcium chloride, calcium formate, calcium acetate, magnesium carbonate, magnesium hydroxide, magnesium oxide, magnesium chloride, magnesium formate, and magnesium acetate can also precipitate stannate ions in the same manner.
[0056] ·Copper separation operation In the copper separation operation in the impurity separation step, copper ions are separated from the post-leaching solution. Hereinafter, a method for separating copper ions from the post-leaching solution will be specifically described.
[0057] -[2]-(1) Cu separation by solvent extraction- The copper precipitation process may involve mixing the post-leaching solution with an organic solvent containing an extractant that extracts copper ions, extracting the copper ions into the extractant and separating them based on the difference in specific gravity, and then separating the copper ions. By adjusting the pH of the solvent, it is possible to adjust the pH so that most of the copper ions are extracted and at least a portion of the zinc ions remain in the zinc ion-containing solution.
[0058] Here, in order to confirm the copper separation conditions, the following experiment was carried out. Copper chloride and zinc chloride were dissolved in the ammonia-containing alkaline leaching solution (1.52 mol-NH 3 A 5% by volume solution of N-salicylideneaniline was used as an extractant, dissolved in kerosene (diluent) at 5% by volume, and used as an extractant-containing organic solvent. The simulated liquid (also called aqueous phase) and the extract phase were placed in a separatory funnel at a volume ratio of 1:2 (O / A ratio = 2) and mixed for 3 minutes to extract the metal components into the extract phase. The mixture was then left to stand, and the entire aqueous phase was removed from the bottom of the separatory funnel. The metal concentration and pH in the aqueous phase were measured, and the metal concentration in the extract phase was calculated from the metal concentration in the aqueous phase and the volumes of the aqueous phase and the extract phase. Next, sulfuric acid acid water was placed in the separatory funnel so that the O / A ratio was 2, and mixed for 3 minutes to back-extract the metal components into the aqueous phase. The mixture was then left to stand, and the entire aqueous phase was removed from the bottom of the separatory funnel, and the metal concentration and pH in the aqueous phase were measured. The metal concentration in the extract phase was calculated from the metal concentration in the aqueous phase and the volumes of the aqueous phase and the extract phase.
[0059] FIG. 5 shows the relationship between pH during extraction and the extraction rate. The extraction rate is the ratio of the amount of metal in the extraction phase to the amount of metal in the aqueous phase and the extraction phase. During extraction, most of the copper ions move to the extraction phase in the pH range of 10.8 or higher. On the other hand, it can be said that zinc ions are partially extracted into the extraction phase at pH 13.0 or lower, but remain in the aqueous phase. Therefore, the pH range in which most of the copper ions are extracted into the extraction phase and zinc ions remain in the aqueous phase is pH 10.8 to pH 13.0. In addition, the optimum pH range for extracting both copper ions and zinc ions into the extraction phase is pH 12.0 to pH 13.3.
[0060] Figure 6 shows the relationship between pH and extraction rate during stripping. During stripping, zinc ions are mostly stripped into the aqueous phase at pH 5.0 or less, while copper ions are stripped at pH 2.5 or less. In the extraction step, the pH is set to 12.0 or more to extract zinc ions and copper ions into the extraction phase, and in the next stripping step, when only zinc is stripped into the aqueous phase, the pH should be set to 5.0-6.0. In addition, in the extraction operation, the pH is adjusted to 10.8 to 13.0, and only copper ions are extracted into the extraction phase. In the subsequent back-extraction operation, zinc ions are back-extracted into the aqueous phase by performing back-extraction at a pH of 5.5 or less, since copper ions are not contained in the aqueous phase.
[0061] Here, N-salicylideneaniline used as an extractant is represented by the following chemical structure, and is a compound having an imine ligand. It is a compound having two sites of oxygen and nitrogen elements, and Zn ions form coordinate bonds with nitrogen and oxygen elements, extracting zinc ions in the aqueous phase into the extraction phase. Extractants that have imine ligands and dissolve in diluents such as kerosene have the effect of extracting metal ions, and examples of such extractants include salicylaldehyde phenylhydrazone, 4-fluoro-N-salicylideneaniline, 2-salicylideneaminophenol, and LIX65N (manufactured by BASF). In addition, there are compounds that have a salen ligand, which is a compound that has two tetradentate oxygen and two nitrogen atoms each, and examples of extractants that dissolve in diluents such as kerosene and have the ability to extract metal ions include N,N'-bis(2-hydroxybenzylidene)ethylenediamine and N,N'-bis(2-hydroxybenzylidene)-1,3-propanediamine.
[0062] [ka]
[0063] As the diluent, in addition to kerosene, hydrophobic organic solvents such as pentane, hexane, octane, and decane can be used.
[0064] -[2]-(2) Cu separation by electrolytic deposition- The copper precipitation operation may be performed by electrolytically precipitating copper ions from the post-leaching solution, thereby separating the copper ions. The potential during electrolytic deposition can be adjusted so that most of the copper ions are precipitated and at least a portion of the zinc ions remain in the zinc ion-containing solution.
[0065] Here, the copper separation conditions are confirmed. In electrolytic deposition, the potential of the working electrode (also called the cathode) is usually set to 200 to 400 mV negative from the equilibrium potential of the oxide and metal, and the target metal is electrolytically deposited. Therefore, from the oxidation-reduction potential-pH diagram of copper, lead, nickel, iron, tin, and zinc, the relationship between the potential and pH (the potential of the working electrode during deposition of each metal) set to 200 mV negative from the equilibrium potential of the oxide and metal is shown in FIG. 7. For example, when metallic copper is deposited from a copper ion-containing solution (pH 10.0), the potential of the working electrode (standard electrode potential) is set to about -320 mV, and when metallic zinc is deposited from a zinc ion-containing solution (pH 10.0), the potential of the working electrode (standard electrode potential) is set to about -1,230 mV.
[0066] To electrolytically deposit metals other than zinc ions from an ammonia-containing alkaline leachate that contains copper ions, zinc ions, nickel ions, and tin ions, when the pH of the ammonia-containing alkaline leachate is 10.0, the potential of the working electrode (standard electrode potential) is set to approximately -860 mV, metals other than zinc metal are first deposited, and then the working electrode is replaced with a new electrode and the potential of the working electrode (standard electrode potential) is set to approximately -1,230 mV, allowing only zinc ions to be deposited on the working electrode as metal ions.
[0067] Alternatively, copper ions, zinc ions, nickel ions, and tin ions are precipitated by electrolytic deposition from an ammonia-containing alkaline leachate containing copper ions, zinc ions, nickel ions, and tin ions at an electrode potential at which zinc precipitates, and then the electrode potential is raised to a potential at which only zinc is eluted, redissolving only the zinc ions and separating them from other metal ions. The post-leachate solution containing the redissolved zinc ions can be transferred to another electrolytic deposition device, where zinc is reprecipitated at an electrode potential at which zinc precipitates, and high-purity metallic zinc can be recovered.
[0068] As described above, by adjusting the potential during electrolytic deposition, it is possible to adjust the potential so that most of the copper ions are precipitated and at least a portion of the zinc ions remain in the zinc ion-containing liquid.
[0069] -[2]-(3) Cu separation by sulfidation- The copper precipitation operation may be carried out by adding one or both of hydrogen sulfide and sulfide ions to the post-leaching solution to adjust the redox potential, and then precipitating the copper ions as copper sulfide, thereby separating the copper ions. By adjusting the redox potential, it is possible to adjust the potential so that most of the copper ions are precipitated and at least a portion of the zinc ions remain in the zinc ion-containing solution.
[0070] Here, in order to confirm the copper separation conditions, the following experiment was carried out. A sodium sulfide aqueous solution was added as a simulant liquid, and the change in metal concentration in the simulant liquid was measured according to pH and redox potential (standard electrode potential). The redox potential (standard electrode potential) at which each metal ion precipitates as a sulfide is different, as shown in Figures 8 and 9. Figures 8 and 9 show that selective precipitation of metal elements is possible by controlling the input amount of sodium sulfide using the redox potential (standard electrode potential). The pH was 13.2 to 13.3, and hardly changed at all.
[0071] From this, by controlling the oxidation-reduction potential (standard electrode potential) in the copper deposition region to a potential lower than 20 to 45 mV and the oxidation-reduction potential (standard electrode potential) in the zinc-nickel simultaneous deposition region to a potential higher than -250 to -270 mV (for example, -100 mV (standard electrode potential)), copper ions can be almost completely removed. Even if a small amount of nickel is contained, nickel ions are precipitated simultaneously with zinc ions, and the oxidation-reduction potential region in which they precipitate is close to the zinc deposition region. Since nickel precipitates at the same time as zinc deposition begins, nickel can be precipitated and separated from zinc by adding a certain amount of sulfide ions after the oxidation-reduction potential (standard electrode potential) reaches -250 mV.
[0072] The redox potential varies depending on the pH. Therefore, it is preferable to use a simulation liquid to investigate in advance the redox potential range in which each metal precipitates as particles, and then adjust the redox potential so that most of the copper ions are precipitated and at least a part of the zinc ions remain in the zinc ion-containing liquid.
[0073] <[3] Zinc electrodeposition process> In the zinc electrolytic deposition process, zinc ions are reduced from the zinc ion-containing solution and electrolytically deposited to recover metallic zinc. Note that the zinc ions can be reduced from the zinc ion-containing solution by adjusting the potential during electrolytic deposition.
[0074] [3]-(1) Electrochemical Deposition of Zinc in Alkaline Solution The zinc ion-containing liquid obtained by the above-mentioned "[2]-(1) Cu separation by solvent extraction," ""[2]-(2) Cu separation by electrodeposition," and ""[2]-(3) Cu separation by sulfidation" is an alkaline liquid, and for example, the zinc ion-containing liquid has a pH of 7.5 to 14.0.
[0075] [3]-(2) Electrochemical Deposition of Zinc in Acidic Solution On the other hand, from the viewpoint of increasing the purity of the recovered metallic zinc, the alkaline zinc ion-containing liquid obtained by the aforementioned "[2]-(1) Cu separation by solvent extraction," "[2]-(2) Cu separation by electrolytic deposition," and "[2]-(3) Cu separation by sulfidation" can be subjected to further extraction and back-extraction processes to obtain an acidic zinc ion-containing liquid, and then metallic zinc can be obtained by electrolytic deposition.
[0076] By going through the extraction step and the back-extraction step, it is possible to further reduce metal ions other than zinc ions, and as a result, it is possible to recover metallic zinc with a higher purity.
[0077] The purity (by mass) of the metallic zinc obtained in the zinc electrolytic deposition process varies depending on the separation state of metal ions other than zinc in the impurity separation process [2], but can be 90.00% or more. The required purity varies depending on the application of the recovered metallic zinc, but can be 98.50% or more. It can also be 99.50% or more.
[0078] [2]-(5) Extraction process and back-extraction process After the impurity separation step and before the zinc electrolytic deposition step, an extraction step is performed in which the zinc ion-containing liquid obtained in the impurity separation step (for example, the alkaline zinc ion-containing liquid obtained by the aforementioned "[2]-(1) Cu separation by solvent extraction," "[2]-(2) Cu separation by electrolytic deposition," and "[2]-(3) Cu separation by sulfidation") is first mixed with an organic solvent containing an extractant that extracts zinc ions and allowed to stand, thereby extracting the zinc ions into the organic solvent and obtaining a zinc ion-containing organic solvent. Next, a back-extraction step is carried out in which the zinc ion-containing organic solvent is mixed with an acidic aqueous solution and allowed to stand, thereby back-extracting the zinc ions into the acidic aqueous solution to obtain a zinc ion-containing acidic aqueous solution. In this way, an acidic zinc ion-containing liquid is obtained, and then metallic zinc can be obtained by electrolytic deposition. The acidic zinc ion-containing liquid has a pH of, for example, -1.0 to 4.0.
[0079] The extractant and solvent used in the extraction process can be the same as those described in the section “[2]-(1) Cu separation by solvent extraction” above.
[0080] [2]-(4) Extraction and back-extraction processes carried out before the copper separation process The extraction step and back extraction step for obtaining an acidic zinc ion-containing solution can also be carried out before the copper separation step. Specifically, the post-leaching solution (for example, the post-leaching solution after the above-mentioned "<[1] Leaching step>", or the post-leaching solution after the above-mentioned "[2]-(0) Tin separation operation" when the post-leaching solution contains tin ions) is first mixed with an organic solvent containing an extractant for extracting zinc ions and copper ions and allowed to stand, thereby performing an extraction operation to extract the zinc ions and copper ions into the organic solvent to obtain an organic solvent containing zinc ions and copper ions. Next, a back-extraction operation is performed in which the zinc ion- and copper ion-containing organic solvent is mixed with an acidic aqueous solution and allowed to stand, thereby back-extracting the zinc ions and copper ions into the acidic aqueous solution to obtain an acidic aqueous solution containing zinc ions and copper ions. Then, copper ions are separated by electrolytic deposition from the zinc ion-copper ion-containing acidic aqueous solution. This allows the production of an acidic zinc ion-containing solution, and the production of metallic zinc by electrolytic deposition. The acidic zinc ion-containing solution has a pH of, for example, -1.0 to 4.0.
[0081] The extractant and solvent used in the extraction process can be the same as those described in the section “[2]-(1) Cu separation by solvent extraction” above.
[0082] <Replacement of alkaline leachate with hydrophobic liquid> In the metallic zinc recovery method according to an embodiment of the present disclosure, after obtaining a post-leaching liquid in the leaching process, a hydrophobic liquid replacement process may be carried out in which a hydrophobic liquid is brought into contact with the residue of the leaching treatment subject, and the alkaline leaching liquid adhering to the surface of the residue is replaced with the hydrophobic liquid.
[0083] In the hydrophobic liquid substitution step, the residue remaining after leaching of the leaching treatment object in the leaching step is brought into contact with a hydrophobic liquid, and the leachate remaining on the surface of the residue is replaced with the hydrophobic liquid.
[0084] In the hydrophobic liquid replacement step, it is preferable to replace the leachate remaining on the surface of the residue with a hydrophobic liquid, separate the leachate that has risen to the surface or settled in the hydrophobic liquid, and then remove the residue from the hydrophobic liquid. Since the hydrophobic liquid and the leachate, which is an aqueous solution, are not easily mixed with each other, the leachate and the hydrophobic liquid can be separated by phase separation using standing or centrifugation, etc. The separated leachate can then be taken out and reused.
[0085] The hydrophobic liquid is a liquid having hydrophobicity, that is, a liquid having a property of having low affinity for water (difficult to dissolve in water or difficult to mix with water). The hydrophobic liquid may be, for example, a liquid having a solubility in water at room temperature (25°C) of 0 g / L or more and 10.0 g / L or less (preferably 0 g / L or more and 5.0 g / L or less). When the solubility of the hydrophobic liquid in water is low, the leachate can be efficiently replaced with the hydrophobic liquid. In addition, the hydrophobic liquid and the leachate can be separated, and the leachate can be easily extracted.
[0086] The term "hydrophobic" includes lipophilicity. The hydrophobic liquid may be, for example, an organic solvent or various oils having hydrophobic properties.
[0087] The solubility of the hydrophobic liquid in water is determined by the solubility published by the manufacturer of the hydrophobic liquid. However, if the solubility is not published, the solubility of the hydrophobic liquid in water is measured as follows. Add 15 mL of water and 15 mL of hydrophobic liquid to a 50 mL centrifuge tube with a stopper, shake at 150 rpm for 1 hour in a 25°C incubator, and then centrifuge the mixture (1,750 G, 5 minutes). After centrifugation, the mixture is left to stand in a thermostatic bath at 25°C for about 1 hour. An aliquot is taken and the amount of solvent in the water is measured by gas chromatography-mass spectrometry (GC / MS), which determines the solubility of the hydrophobic liquid in water.
[0088] The boiling point of the hydrophobic liquid is preferably lower than the boiling point of the leaching liquid under isobaric conditions and higher than the operating temperature of the hydrophobic liquid at the pressure of the hydrophobic liquid replacement step.
[0089] For example, when the temperature of the leaching liquid is room temperature (25°C), the boiling point of the hydrophobic liquid is preferably 40°C or higher and lower than 200°C under the same pressure. The upper limit of the boiling point is more preferably lower than 100°C, and even more preferably 95°C or lower. When the temperature of the leaching liquid is higher than 100°C and lower than 150°C, the boiling point of the hydrophobic liquid is preferably 30 to 100°C higher than that of the leaching liquid. Specifically, when the leaching is carried out at room temperature (25°C) and normal pressure, the boiling point of the hydrophobic liquid is preferably 40°C to 95°C at normal pressure. By setting the boiling point of the hydrophobic liquid within the above range, the hydrophobic liquid can be easily removed by evaporation and separated from the residue, which reduces the energy cost for removing the hydrophobic liquid from the residue in the residual hydrophobic liquid removal step.
[0090] There are no particular limitations on the hydrophobic liquid as long as it satisfies the above conditions. Examples of hydrophobic liquids include chlorine-based hydrophobic liquids (trichloroethylene, tetrachloroethylene, dichloromethane, etc.), fluorine-based hydrophobic liquids (dichloropentafluoropropane (HCFC), hydrofluorocarbons (HFCs), hydrofluoroethers (HFEs), 1-ethoxy-1 ,1,2,2,3,3,4,4,4-nonafluorobutane, etc.), bromine-based hydrophobic liquids (1- Bromopropane, etc.), creosote oil, nitrobenzene, carbon disulfide, chlorobenzene, normal hexane, normal pentane, kerosene, etc.
[0091] In the hydrophobic liquid replacement step, the method of contacting the residue with the hydrophobic liquid is not particularly limited, and examples thereof include a method of immersing the residue in the hydrophobic liquid, a method of spraying the hydrophobic liquid on the residue, and a method of repeatedly contacting the residue with the hydrophobic liquid. An example of a method for immersing the residue in a hydrophobic liquid is a method in which the residue is immersed in a hydrophobic liquid contained in a hydrophobic liquid replacement container. An example of a method for spraying the hydrophobic liquid on the residue is a method in which the hydrophobic liquid is sprayed on a pile of the residue in a yard. Examples of methods for repeatedly contacting the residue with a hydrophobic liquid include a method in which the residue is immersed in the hydrophobic liquid contained in a hydrophobic liquid replacement container while circulating the liquid, and a method in which the hydrophobic liquid is sprayed onto a pile of residue in a yard and the sprayed hydrophobic liquid is recovered and circulated. Among these, from the viewpoint of efficient replacement with the hydrophobic liquid, it is preferable to employ a method of contacting the residue with the hydrophobic liquid by immersing the residue in the hydrophobic liquid.
[0092] After the hydrophobic liquid replacement step, the residue may be heated to volatilize and remove the hydrophobic liquid remaining on the surface of the residue.
[0093] Although scale, dust and sludge have a larger specific surface area than scrap iron,[1] the reactions in the leaching process are the same, and metallic zinc can be recovered from scale, dust and sludge in the same way as from scrap iron. EXAMPLES
[0094] The present disclosure will be described more specifically below with reference to examples, but the present disclosure is not limited to these examples.
[0095] <Example 1: No. 1-1 to 1-9 (simulation experiment)> [0]-(1) Materials to be leached containing Cu and Zn [1]-(1) <Leaching process> Ammonia-containing leachate pH 7.5~14.0 [2]-(1) <Impurity separation process> Solvent extraction Cu separation with alkali [3]-(1) <Zinc electrodeposition process> Alkaline solution Zinc electrodeposition -Leaching process- In a 10-L sealed container, add 3 g of copper powder, 3 g of zinc powder, and 0.3 L of an aqueous ammonium solution (alkali leaching solution) containing ammonium sulfate and adjusted to the pH value (range of pH 7.5 to 13.7) shown in Table 1 (30 g-NH 3 / L) was added, the gas phase was replaced with oxygen, and the mixture was shaken for two days to leach copper and zinc, and the leachate containing copper ions and zinc ions was collected. -Impurity separation process- Next, 0.2 L of the recovered post-leaching solution was placed in a separatory funnel, and 3 L of an extract (50 g / L) made by dissolving an extractant (N-salicylideneaniline) in kerosene (diluent) was added, stirred for 2 minutes, and copper ions and a part of zinc ions were transferred to the extraction phase, and then allowed to stand. The aqueous phase containing zinc ions (zinc ion-containing solution) was separated from the bottom of the separatory funnel, and the zinc ion-containing solution was recovered. -Zinc electrodeposition process- Next, the potential between the working electrode and the reference electrode was controlled to a desired value using a potentiostat device, and electrolytic deposition was performed. The zinc ion-containing solution was adjusted to the potential (standard electrode potential) of the working electrode to the voltage listed in Table 1 using the potentiostat function, and electrolytic deposition was performed for 6 hours, depositing metallic zinc on the surface of the titanium plate placed on the working electrode side. A platinum-plated titanium electrode was used as the counter electrode.
[0096] The surface of the titanium plate on the working electrode side was analyzed by fluorescent X-ray diffraction, and the zinc concentration in the metal precipitated on the surface of the titanium plate was calculated from the content of metals other than titanium, to evaluate the purity of the metallic zinc. The results are shown in Table 1.
[0097] [Table 1]
[0098] In the leaching process, zinc and copper were leached at pH 7.5 to 13.7. However, in the impurity separation process, the pH range in which most of the copper ions can be transferred to the extraction phase (N-salicylideneaniline) and some zinc can remain in the leaching solution after leaching was in the pH range of 10.1 to 12.8. In the zinc electrodeposition process, the pH range in which the purity of metallic zinc was 90.00% or more was in the pH range of 10.1 to 12.8. From the above, when the pH is almost constant from the leaching step to the zinc electrolytic deposition step and N-salicylideneaniline is used as the extractant, a pH of 10.1 to 12.8 is suitable. On the other hand, when an acid or alkali is added to the leachate to be treated in the impurity separation step to adjust the pH to 10.1 to 12.8, the pH of the leaching step can be from 7.5 to 13.7.
[0099] <Example 2: No. 2-1 to 2-2 (simulation experiment)> [0]-(1) Materials to be leached containing Cu and Zn [1]-(1) <Leaching process> Ammonia-containing leachate pH 7.5~14.0 [2]-(2) <Impurity separation process> Cu separation using electrolytic deposition and alkali [3]-(1) <Zinc electrodeposition process> Alkaline solution Zinc electrodeposition -Leaching process- The leaching process was carried out in the same manner as in No. 1-2 (Comparative Example) and No. 1-4 (Example), and the post-leaching solution was collected. -Impurity separation process- Next, the potentials of the working electrodes of the post-leaching solutions (standard electrode potentials) were adjusted to -400mV and -550mV, respectively, using a potentiostat device, and electrolytic deposition was carried out for 6 hours to deposit metallic copper on the surface of the titanium plate placed on the working electrode side. -Zinc electrodeposition process- Next, the titanium plate on the working electrode side was removed, a new titanium plate was placed on the working electrode, and the potentials (standard electrode potentials) were adjusted to -1,140 mV and -1,290 mV, respectively, and electrolytic deposition was performed for 6 hours to deposit metallic zinc on the surface of the titanium plate placed on the working electrode side. A platinum-plated titanium electrode was used as the counter electrode.
[0100] The surface of the titanium plate on the working electrode side was analyzed by fluorescent X-ray diffraction, and the zinc concentration in the metal precipitated on the surface of the titanium plate was calculated from the content of metals other than titanium, to evaluate the purity of the metallic zinc. As a result, high purity metallic zinc of 99.7% and 99.8% was obtained in No. 2-1 (Example) and No. 2-2 (Example), respectively.
[0101] [Table 2]
[0102] <Example 3: No. 3-1 to 3-2 (simulation experiment)> [0]-(1) Materials to be leached containing Cu and Zn [1]-(1) <Leaching process> Ammonia-containing leachate pH 7.5~14.0 [2]-(3) <Impurity separation process> Sulfidation Cu separation with alkali [3]-(1) <Zinc electrodeposition process> Alkaline solution Zinc electrodeposition -Leaching process- The leaching process was carried out in the same manner as in No. 1-2 (Comparative Example) and No. 1-8 (Comparative Example), and the post-leaching solution was collected. -Impurity separation process- Next, an aqueous solution of sodium sulfide was added to the post-leaching solution, and an aqueous solution of sodium hydrogen sulfide was added until the redox potential (standard electrode potential) became 190 mV and -100 mV, respectively, to precipitate copper ions as sulfides. The pH was adjusted to 8.3 and 13.2 by adding dilute sulfuric acid or an aqueous solution of sodium hydroxide. The precipitated sulfides were filtered to obtain a filtrate (zinc ion-containing solution). -Zinc electrodeposition process- Next, the filtrate (zinc ion-containing solution) was adjusted to -1,140 mV and -1,430 mV (standard electrode potential) of the working electrode using a potentiostat device, and electrolytic deposition was performed for 6 hours to deposit metallic zinc on the surface of the titanium plate placed on the working electrode side. A platinum-plated titanium electrode was used as the counter electrode.
[0103] The surface of the titanium plate on the working electrode side was analyzed by fluorescent X-ray diffraction, and the zinc concentration in the metal precipitated on the surface of the titanium plate was calculated from the content of metals other than titanium, and the purity of the metallic zinc was evaluated. As a result, high purity metallic zinc of 99.6% and 99.7% was obtained in No. 3-1 (Example) and No. 3-2 (Example), respectively.
[0104] [Table 3]
[0105] <Example 4: No. 4-1 (simulation experiment)> [0]-(1) Materials to be leached containing Cu and Zn [1]-(1) <Leaching process> Ammonia-containing leachate pH 7.5~14.0 [2]-(4) <Impurity separation process> Extraction (alkali) → Stripping (acid) → Electrolytic Cu deposition separation (acid) [3]-(2) <Zinc electrodeposition process> Acid solution Zinc electrodeposition -Leaching process- The leaching process was carried out in the same manner as in No. 1-7 (Example), and the post-leaching solution was recovered. -Impurity separation process- Next, 0.2L of the post-leaching solution (pH 12.8) was placed in a separatory funnel, and 3L of an extractant (N-salicylideneaniline) dissolved in kerosene (diluent) (50g / L) was added, stirred for 2 minutes, and copper ions and zinc ions were extracted into the extract phase, and then allowed to stand. After separating the aqueous phase from the bottom of the separatory funnel, 0.2L of sulfuric acid acid water was added from the top of the separatory funnel, stirred for 2 minutes, and most of the copper ions and zinc ions were back-extracted into the aqueous phase, and allowed to stand. Then, the aqueous phase (back-extraction phase) was separated and collected from the bottom of the separatory funnel. The pH of the back-extraction solution collected was pH 1.6. Next, the back-extraction solution was adjusted to 0mV (standard electrode potential) of the titanium plate on the working electrode side with a potentiostat device, and electrolytic deposition was performed for 6 hours, and metallic copper was deposited on the surface of the titanium plate installed on the working electrode side. In addition, a platinum-plated titanium electrode was used as the counter electrode. -Zinc electrodeposition process- After that, the titanium plate on the working electrode side was removed, a new titanium plate was placed on the working electrode side of the potentiostat device, the potential of the working electrode (standard electrode potential) was adjusted to -1,000 mV, and electrolytic deposition was performed for 6 hours to deposit metallic zinc on the surface of the titanium plate placed on the working electrode side. A platinum-plated titanium electrode was used as the counter electrode.
[0106] The surface of the titanium plate on the working electrode side was analyzed by fluorescent X-ray diffraction, and the zinc concentration in the metal precipitated on the surface of the titanium plate was calculated from the content of metals other than titanium, and the purity of the metallic zinc was evaluated. As a result, in No. 4-1 (Example), a high purity metallic zinc of 99.8% was obtained.
[0107] [Table 4]
[0108] <Example 5: No. 5-1 (simulation experiment)> [0]-(1) Materials to be leached containing Cu and Zn [1]-(1) <Leaching process> Ammonia-containing leachate pH 7.5~14.0 [2]-(3) <Impurity separation process> Sulfidation Cu separation with alkali [2]-(5) <Impurity separation process> Extraction (alkali) → back-extraction (acid) [3]-(2) <Zinc electrodeposition process> Acid solution Zinc electrodeposition -Leaching process- The leaching process was carried out in the same manner as in No. 1-8 (Comparative Example), and the post-leaching solution was recovered. -Impurity separation process- Next, an aqueous solution of sodium sulfide was added to the post-leaching solution, and an aqueous solution of sodium hydrogen sulfide was added until the oxidation-reduction potential (standard electrode potential) was -100 mV, and copper ions were precipitated as sulfides. The pH was adjusted to pH 13.2 by adding an aqueous solution of sodium hydroxide. The precipitated sulfide was filtered to obtain a filtrate. 0.3 L of the filtrate was placed in a separatory funnel, and 3 L of an extract (50 g / L) in which an extractant (N-salicylideneaniline) was dissolved in kerosene (diluent) was added, stirred for 2 minutes, and most of the zinc ions were extracted into the extract phase, and then allowed to stand. After separating the aqueous phase from the bottom of the separatory funnel, 0.3 L of sulfuric acid acid water was added from the top of the separatory funnel, stirred for 2 minutes, and most of the zinc ions were back-extracted into the aqueous phase, and then allowed to stand. Then, the aqueous phase (back-extraction phase) was separated and collected from the bottom of the separatory funnel. The pH of the back-extraction liquid collected was pH 1.6. -Zinc electrodeposition process- After that, the potential (standard electrode potential) of the titanium plate on the working electrode side of the stripping solution was adjusted to -1,000 mV using a potentiostat device, and electrolytic deposition was performed for 6 hours to deposit metallic zinc on the surface of the titanium plate placed on the working electrode side. A platinum-plated titanium electrode was used as the counter electrode.
[0109] The surface of the titanium plate on the working electrode side was analyzed by fluorescent X-ray diffraction, and the zinc concentration in the metal precipitated on the surface of the titanium plate was calculated from the content of metals other than titanium, and the purity of the metallic zinc was evaluated. As a result, in No. 5-1 (Example), a high purity metallic zinc of 99.9% was obtained.
[0110] [Table 5]
[0111] <Example 6: No. 6-1 to 6-5 (simulation experiment)> [0]-(2) Materials to be leached containing Cu, Zn, and Sn [1]-(2) <Leaching process> Ammonia-containing leachate pH 12.5~14.0 [2]-(0) <Impurity separation process> Ca, Mg-added stannate precipitation Sn separation with alkali [2]-(3) <Impurity separation process> Sulfidation Cu separation with alkali [3]-(1) <Zinc electrodeposition process> Alkaline solution Zinc electrodeposition -Leaching process- In a 10-L sealed container, 3 g of copper powder, 3 g of zinc powder, 3 g of tin powder, and 0.4 L of an aqueous solution of ammonium sulfate (alkaline leaching solution) adjusted to pH 13.2 (30 g-NH 3 / L) was added, the gas phase was replaced with oxygen, and the mixture was then shaken for two days to leach copper, zinc, and tin, and the leaching solution containing copper ions, zinc ions, and tin ions was collected. -Impurity separation process- Next, a tin ion precipitant (one or more of calcium carbonate powder, quicklime powder, and magnesium oxide powder) shown in Table 6 was added to 0.3 L of the recovered leaching solution, and tin ions were precipitated as calcium stannate or magnesium stannate. The precipitate was then filtered, and the tin-separated leaching solution from which tin ions had been separated was recovered. Thereafter, an aqueous sodium sulfide solution was added to the leaching solution from which tin had been separated, and an aqueous sodium hydrogen sulfide solution was added until the oxidation-reduction potential (standard electrode potential) shown in Table 6 was reached, thereby precipitating copper ions as sulfides. The pH was adjusted to pH 13.2 by adding an aqueous sodium hydroxide solution. The precipitated sulfides were filtered to obtain a filtrate (zinc ion-containing solution). -Zinc electrodeposition process- Next, the filtrate (zinc ion-containing solution) was electrolytically deposited for 6 hours by adjusting the potential (standard electrode potential) of the titanium plate on the working electrode side to -1,430 mV using a potentiostat device, and metallic zinc was deposited on the surface of the titanium plate placed on the working electrode side. A platinum-plated titanium electrode was used as the counter electrode.
[0112] The surface of the titanium plate on the working electrode side was analyzed by fluorescent X-ray diffraction, and the zinc concentration in the metal precipitated on the surface of the titanium plate was calculated from the content of metals other than titanium, and the purity of the metallic zinc was evaluated. As a result, high purity metallic zinc of 99.1% to 100.0% was obtained.
[0113] [Table 6]
[0114] <Example 7-1> [0]-(2) Materials to be leached containing Cu, Zn, and Sn [1]-(2) <Leaching process> Ammonia-containing leachate pH 12.5~14.0 (Replacement of alkaline leachate with hydrophobic liquid: not carried out) [2]-(0) <Impurity separation process> Ca, Mg-added stannate precipitation Sn separation with alkali [2]-(3) <Impurity separation process> Sulfidation Cu separation with alkali [3]-(1) <Zinc electrodeposition process> Alkaline solution Zinc electrodeposition -Leaching process- Thin-plate iron scrap containing a mixture of enamel-coated copper wire, painted zinc-nickel-plated steel sheet, painted zinc-plated steel sheet, and painted tin-plated steel sheet was placed in an open electric furnace and heated for 30 minutes at 500°C to remove the enamel coating and painted parts. 800 g of the heat-treated iron scrap was then immersed in an alkaline leachate (38 g-NH 3 The leaching was carried out for 5 hours in a sealed container containing 2L of ammonium nitrate (controlled at pH 10.0, DO (dissolved oxygen concentration) 10mg / L). After leaching, the iron scrap residue was magnetically attracted with an electromagnet and removed. The leachate remaining in the sealed container was filtered to remove solids, and the post-leaching solution was obtained.
[0115] (Confirmation of iron scrap residue and post-leach liquid) The removed iron scrap residue was immersed in pure water (2 L) in a water washing container, and the alkaline leachate remaining on the surface of the iron scrap residue was washed with the pure water to obtain a washing solution. The sulfate ion concentration in this washing solution was measured, and the amount of residual leachate adhering to the surface of the removed iron scrap residue per unit area was calculated from the concentration, which was 120 mL / m 2 It was. The metal concentration in the leaching solution was as shown in Table 7-2. The solid matter obtained by filtration was analyzed and found to contain iron and nickel. The nickel content in the iron scrap residue was reduced from 0.20% before the leaching treatment to 0.03% after the leaching treatment as shown in Table 7-1. However, the leaching solution contained only 25 mg / L of nickel. This confirmed that almost no nickel originating from the zinc-nickel plated steel sheet was dissolved in the leaching solution.
[0116] -Impurity separation process- Next, 0.4g of calcium carbonate powder was added to the collected leaching solution to precipitate the tin ions in the leaching solution as calcium stannate. The precipitate and the solids remaining in the leaching process were separated by filtration to obtain the leaching solution from which tin had been separated. The metal concentrations of the leaching solution from which tin had been separated are shown in Table 7-2. Next, while adjusting the pH to pH 10.0, an aqueous sodium sulfide solution was added to the leaching solution after the tin separation, and the oxidation-reduction potential (standard electrode potential) was adjusted to -60 mV, which is the potential at which nickel ions begin to precipitate as sulfides, and copper ions were precipitated as sulfides. After that, 0.006 g of an aqueous sodium sulfide solution was further added, and nickel and some of the zinc were precipitated as sulfides. The precipitated calcium stannate and sulfides were filtered to obtain a zinc ion-containing solution. The metal ion concentrations of the zinc ion-containing solution were as shown in Table 7-2. -Zinc electrodeposition process- Next, the potential (standard electrode potential) of the working electrode was adjusted to -1,230 mV using a potentiostat device, and the zinc ion-containing solution was electrolytically deposited for 6 hours to deposit metallic zinc on the surface of the titanium plate placed on the working electrode side. A platinum-plated titanium electrode was used as the counter electrode.
[0117] The surface of the titanium plate on the working electrode side was analyzed by fluorescent X-ray diffraction, and the zinc concentration in the metal precipitated on the surface of the titanium plate was calculated from the content of metals other than titanium, and the purity of the metallic zinc was evaluated. As a result, high-purity metallic zinc of 99.8% was obtained. In this way, it was confirmed that high-purity metallic zinc can be obtained by separating metal elements other than zinc in the impurity separation process.
[0118] The removal rates of each element in the recovered iron scrap residue were as follows, as shown in Table 7-1: Cu removal rate: 74%, Zn removal rate: 87%, Ni removal rate: 85%, Sn removal rate: 20%.
[0119] [Table 7-1]
[0120] [Table 7-2]
[0121] <Example 7-2> [0]-(2) Materials to be leached containing Cu, Zn, and Sn [1]-(2) <Leaching process> Ammonia-containing leachate pH 12.5~14.0 Replacement of alkaline leachate with hydrophobic liquid [2]-(0) <Impurity separation process> Ca, Mg-added stannate precipitation Sn separation with alkali [2]-(3) <Impurity separation process> Sulfidation Cu separation with alkali [3]-(1) <Zinc electrodeposition process> Alkaline solution Zinc electrodeposition -Leaching process- The leaching step was carried out in the same manner as in Example 7-1, and after leaching, the iron scrap residue was taken out and a post-leaching solution was obtained. -Replacement of alkaline leachate with hydrophobic liquid- The iron scrap residue was placed in 2 L of hydrophobic liquid (1-bromopropane with 0.21 g / L of surfactant (Na-sulfonate) dissolved therein) in a hydrophobic liquid replacement container (sealed container) and immersed for 1 minute to separate the alkaline leachate adhering to the surface of the iron scrap residue. The alkaline leachate that had risen to the surface of the hydrophobic liquid was removed with a dropper, and the iron scrap residue was magnetically attracted with an electromagnet and removed from the hydrophobic liquid. The removed iron scrap residue was placed again in the hydrophobic liquid and immersed for 1 minute to further separate the leachate adhering to the surface of the iron scrap residue. The alkaline leachate that had risen to the surface of the hydrophobic liquid was removed with a dropper, and the iron scrap residue was magnetically attracted with an electromagnet and removed from the hydrophobic liquid. In this way, replacement of the alkaline leachate with the hydrophobic liquid was performed twice. Next, the scrap iron residue removed from the hydrophobic liquid replacement container was immersed in pure water (2 L) in a water washing container, and the alkaline leachate remaining on the surface of the scrap iron residue was washed with the pure water to obtain a washing liquid. The sulfate ion concentration in this washing liquid was measured, and the amount of residual leachate adhering to the surface of the scrap iron residue removed from the hydrophobic liquid replacement container per unit area was calculated from the concentration, resulting in a value of "8 mL / m 2 " It was. In Example 7-1, the amount of residual leachate was 120 mL / m 2 " In other words, compared to Example 7-1, the amount of residual leachate was reduced by 93% by replacing it with a hydrophobic liquid.
[0122] -Impurity separation process- Next, 0.4g of calcium carbonate powder was added to the collected leaching solution to precipitate the tin ions in the leaching solution as calcium stannate. The precipitate and the solids remaining in the leaching process were separated by filtration to obtain the leaching solution from which tin had been separated. The metal concentrations of the leaching solution from which tin had been separated are shown in Table 7-2. Next, while adjusting the pH to pH 10.0, an aqueous sodium sulfide solution was added to the leaching solution after the tin separation, and the oxidation-reduction potential (standard electrode potential) was adjusted to -60 mV, which is the potential at which nickel ions begin to precipitate as sulfides, and copper ions were precipitated as sulfides. After that, 0.006 g of an aqueous sodium sulfide solution was further added, and nickel and some of the zinc were precipitated as sulfides. The precipitated calcium stannate and sulfides were filtered to obtain a zinc ion-containing solution. The metal ion concentrations of the zinc ion-containing solution were as shown in Table 7-2. -Zinc electrodeposition process- Next, the potential (standard electrode potential) of the zinc ion-containing liquid on the working electrode side was adjusted to -1,230 mV using a potentiostat device, and electrolytic deposition was performed for 6 hours to deposit metallic zinc on the surface of the titanium plate placed on the working electrode side.
[0123] The surface of the titanium plate on the working electrode side was analyzed by fluorescent X-ray diffraction, and the zinc concentration in the metal precipitated on the surface of the titanium plate was calculated from the content of metals other than titanium, and the purity of the metallic zinc was evaluated. As a result, high-purity metallic zinc of 99.6% was obtained. In this way, it was confirmed that high-purity metallic zinc can be obtained by separating metal elements other than zinc in the impurity separation process.
[0124] The removal rates of each element in the recovered iron scrap residue were as follows: Cu removal rate: 80%, Zn removal rate: 91%, Ni removal rate: 75%, Sn removal rate: 20%. In addition, the alkaline leachate remaining on the surface of the iron scrap residue was reduced by 93% (112 ml / m 2 ) was reduced, which also reduced the amount of water used to wash the scrap iron residue after the leaching process and the amount of waste washing liquid to be treated.
Claims
1. A method for recovering metallic zinc from a solid leaching treatment target that contains an iron component and at least zinc and copper in the form of metal or oxide, comprising the steps of: a leaching step of contacting the object of leaching treatment with an alkaline leaching solution containing ammonium ions and having a pH of 7.5 to 14.0 to obtain a leaching solution in which the zinc and copper are leached into the alkaline leaching solution as zinc ions and copper ions; an impurity separation step of subjecting the post-leaching solution to a copper separation operation for separating the copper ions to obtain a zinc ion-containing solution containing the zinc ions; a zinc electrolytic deposition step of reducing and electrolytically depositing the zinc ions from the zinc ion-containing solution to recover metallic zinc having a purity of 90.00 mass% or more; The method for recovering metallic zinc comprising the steps of:
2. 2. The method for recovering metallic zinc according to claim 1, wherein the object of leaching treatment further contains tin in metallic form.
3. the leaching step is a step of obtaining a leaching solution by leaching the zinc, copper and tin into the alkaline leaching solution as zinc ions, copper ions and tin ions, the alkaline leaching solution having a pH of 12.5 to 14.0; The impurity separation step is a step of subjecting the leaching solution to a tin separation step of separating the tin ions into at least one of calcium stannate and magnesium stannate by adding at least one salt selected from the group consisting of calcium or magnesium carbonate, hydroxide, oxide, chloride, formate, and acetate prior to the copper separation step, and subjecting the leaching solution that has been subjected to the tin separation step to the copper separation step. The method for recovering metallic zinc according to claim 2.
4. 2. The method for recovering metallic zinc according to claim 1, wherein the copper separation operation in the impurity separation step is an operation of mixing the post-leaching solution with an organic solvent containing an extractant for extracting copper ions, extracting the copper ions into the extractant, and separating the copper ions based on the difference in specific gravity, thereby separating the copper ions.
5. 2. The method for recovering metallic zinc according to claim 1, wherein the copper separation operation in the impurity separation step is an operation of separating the copper ions by precipitating the copper ions from the post-leaching solution by electrolytic deposition.
6. 2. The method for recovering metallic zinc according to claim 1, wherein the copper separation operation in the impurity separation step is an operation of separating the copper ions by adding one or both of hydrogen sulfide and sulfide ions to the post-leaching solution to adjust the oxidation-reduction potential and precipitating the copper ions as copper sulfide, thereby separating the copper ions.
7. 2. The method for recovering metallic zinc according to claim 1, wherein the zinc ion-containing liquid has a pH of 7.5 to 14.0 in the zinc electrolytic deposition step.
8. After the impurity separation step and before the zinc electrodeposition step, an extraction step of mixing the zinc ion-containing liquid obtained in the impurity separation step with an organic solvent containing an extractant for extracting zinc ions and allowing the mixture to stand, thereby extracting the zinc ions into the organic solvent to obtain a zinc ion-containing organic solvent; a back-extraction step of mixing the zinc ion-containing organic solvent with an acidic aqueous solution and allowing the mixture to stand, thereby back-extracting the zinc ions into the acidic aqueous solution to obtain a zinc ion-containing acidic aqueous solution, The method for recovering metallic zinc according to any one of claims 4 to 6, wherein the zinc electrodeposition step uses the zinc ion-containing acidic aqueous solution as the zinc ion-containing liquid.
9. The copper separation operation in the impurity separation step is an extraction operation in which the post-leaching solution is mixed with an organic solvent containing an extractant for extracting zinc ions and copper ions, and the mixture is allowed to stand, thereby extracting the zinc ions and the copper ions into the organic solvent to obtain an organic solvent containing zinc ions and copper ions; a back-extraction operation in which the zinc ion and copper ion-containing organic solvent is mixed with an acidic aqueous solution and allowed to stand, thereby back-extracting the zinc ion and the copper ion into the acidic aqueous solution to obtain an acidic aqueous solution containing zinc ion and copper ion; The copper ions are separated by electrolytic deposition from the zinc ion- and copper ion-containing acidic aqueous solution to obtain a zinc ion-containing acidic aqueous solution containing the zinc ions.
2. The method for recovering metallic zinc according to claim 1, wherein the zinc electrodeposition step uses a zinc ion-containing acidic aqueous solution as the zinc ion-containing liquid.
10. The method for recovering metallic zinc according to claim 9, wherein the zinc ion- and copper ion-containing acidic aqueous solution has a pH of -1.0 to 4.
0.
11. 2. The method for recovering metallic zinc according to claim 1, further comprising a hydrophobic liquid replacement step of contacting a residue of the leaching treatment object after the zinc and copper have been leached into the alkaline leaching solution in the leaching step with a hydrophobic liquid, thereby replacing the alkaline leaching solution adhering to the surface of the residue with the hydrophobic liquid.
12. The method for recovering metallic zinc according to claim 11, wherein the boiling point of the hydrophobic liquid at normal pressure is 40°C to 95°C.
Citation Information
Patent Citations
Method for recovering zinc and lead from flue dust generated in electric steelmaking, method for recirculating refined metal into furnace and apparatus for executing this method
JP1993255772A
Method for separating and recovering zinc from ferroscrap
JP1993271820A
Method for separating and recovering copper, iron and the like from motor scrap and the like
JP1994240373A
Method for purifying electrolytic solution in univalent copper electrolytic winning process
JP2006057137A
Method for manufacturing a metal
JP2014040639A
